Impact of Human Genetic Variation on C-Reactive Protein Concentrations and Acute Appendicitis - Ricaño-Ponce, Isis; Peeters, Toon; Matzaraki, Vasiliki; Houben, Bert; Achten, Ruth; Cools, Peter; Netea, Mihai G.; Gyssens, Inge C.; Kumar, Vinod (Frontiers in Immunology, 2022)
Background: Acute appendicitis is one of the most common abdominal emergencies worldwide. Both environmental and genetic factors contribute to the disease. C-Reactive protein is (CRP) is an important biomarker in the diagnosis of acute appendicitis. CRP-concentrations are significantly affected by genetic variation. However, whether such genetic variation is causally related to appendicitis risk remains unclear. In this study, the causal relationship between SNPs associated with circulating CRP-concentrations and the risk and severity of acute appendicitis was investigated. Methods: CRP-concentrations in serum of appendicitis patients (n=325) were measured. Appendicitis was categorized as complicated/uncomplicated and gangrenous/non-gangrenous. Imputed SNP data (n=286) were generated. GWAS on CRP-concentrations and appendicitis severity was performed. Intersection and colocalization of the GWAS results were performed with appendicitis and CRP-associated loci from the Pan-UKBB cohort. A functional-genomics approach to prioritize genes was employed. Results: Seven percent of significant CRP-QTLs that were previously identified in a large cohort of healthy individuals were replicated in our small patient cohort. A significant enrichment of CRP QTLs in loci-associated to appendicitis was observed. Among these shared loci, two top loci at chromosomes 1q41 and at 8p23.1 were characterized. The top SNP at chromosome 1q41 is located within the promoter of H2.0 Like Homeobox (HLX) gene, which is involved in blood cells differentiation, liver, and gut organogenesis. The expression of HLX is increased in the appendix of appendicitis patients compared to controls. The locus at 8p23.1 contains multiple genes, including Cathepsin B (CTSB), which is overexpressed in appendix tissue from appendicitis patients. The risk allele of the top SNP in this locus also increases CTSB expression in sigmoid colon of healthy individuals. CTSB is involved in collagen degradation, MHC class II antigen presentation, and neutrophil degranulation. Conclusions: The results of this study prioritize HLX and CTSB as potential causal genes for appendicitis and suggest a shared genetic mechanism between appendicitis and the determination of circulating CRP-concentrations.